Importance of Boundary Processes for Heat Uptake in the Subpolar North Atlantic. Issue 9 (1st September 2020) - Desbruyères, D. G.; Sinha, B.; McDonagh, E. L.; Josey, S. A.; Holliday, N. P.; Smeed, D. A.; New, A. L.; Megann, A.; Moat, B. I.
Abstract: The decadal to multidecadal temperature variability of the intermediate (700–2, 000 m) North Atlantic Subpolar Gyre (SPG) significantly imprints the global pattern of ocean heat uptake. Here, the origins and dominant pathways of this variability are investigated with an ocean analysis product (EN4), an ocean state estimate (ECCOv4), and idealized modeling approaches. Sustained increases and decreases of intermediate temperature in the SPG correlate with long‐lasting warm and cold states of the upper ocean with the largest anomalous vertical heat exchanges confined to the vicinity of continental boundaries and strong ocean currents. In particular, vertical diffusive processes along the boundaries of the Labrador, Irminger, and Newfoundland basins are important drivers of the recent intermediate depth warming trend observed during 1996–2014. The overall effect of those processes is captured by a one‐dimensional diffusive model with appropriate boundary‐like parametrization and demonstrated through the boundary‐focused downward propagation of a passive tracer in a 3‐D numerical simulation. Our results imply that the slow and quasi‐periodic ventilation of intermediate thermohaline properties and associated heat uptake in the SPG are not strictly driven by convection‐restratification events in the open seas but also receives a key contribution from boundary sinking and mixing. Increased skill for modeling and predicting intermediate‐depth ocean properties in the North Atlantic will hence require the appropriate representation of surface‐deep dynamical connections within the boundary currents encircling Greenland and Newfoundland. Plain Language Summary: The subarctic basins of the North Atlantic Ocean play a fundamental role in regulating the climate system. This occurs notably throughout direct connections between the ocean surface (and hence the atmosphere) and deep oceanic layers, which enable the long‐term sequestration and subsequent propagation of physical and biogeochemical anomalies (e.g., heat and carbon). Here, we employ a multitool approach to investigate the mechanisms by which anomalous heat can penetrate downward in this region. Historical observations gathered during 1950–2016 and combined with idealized modeling strategy suggest that decadal temperature trends in the intermediate layer strongly correlate with long‐lasting warm and cold states of the upper ocean, suggesting potential for first‐order predictability. Focusing on the well‐observed era (1992–2016) using a realistic ocean reanalysis and tracer propagation experiments in a numerical model, we show that the associated downward penetration of temperature anomalies receives an important contribution from mixing and advection within the energetic boundary currents of the Labrador Sea, Irminger Sea, and Newfoundland basin. Key Points: A causal and lagged relationship exists between basin‐mean upper and intermediate decadal temperature changes in the subpolar North Atlantic Variability in vertical heat transport convergence is dominant within the energetic boundary currents of the subpolar North Atlantic Open‐ocean deep convection is not a unique pathway for slow thermohaline ventilation and heat uptake in the subpolar North Atlantic